An Interdisciplinary Insight Into the Human Dimension in Fisheries Models. A Systematic Literature Review in a European Union Context - Weber, Charlotte Teresa; Borit, Melania; Aschan, Michaela (Frontiers in Marine Science, 2019)
Fisheries are complex adaptive social-ecological systems (SES) that consist of interlinked human and ecosystems. They have mainly been studied by the natural sciences and focused on the ecosystem. However, rising concerns about sustainability and increasing complexity of societal challenges often require an understanding of fisheries in a SES context. For this purpose, the study of the human system should be expanded within fisheries science. Models are currently the most common method used in the field and these need to include the human dimension, alongside the ecosystem, when addressing fisheries systems as SES. The human dimension is an umbrella term for the complex web of human processes and it is captured by disciplines from the social sciences and the humanities. Consequently, capturing and synthesizing the variety of disciplines involved in the human dimension, and integrating them into fisheries models, requires an interdisciplinary approach. This study attempts to assess the presence of the human dimension in fisheries models applied to a European Union context and to evaluate interdisciplinarity within modelled human dimension aspects through a systematic review and qualitative analysis. Within 31 modelling publications, 20 different human dimension aspects could be identified within the categories of social phenomena, social processes, and individual attributes. Most of the human dimension aspects were modelled in an interdisciplinary manner in mathematical, statistical, simulation, or conceptual models. Yet, predominantly through the use of economic and environmental variables. We conclude that there is potential for the expansion of the human dimension and interdisciplinarity in fisheries models. To reach this potential, one should consider early involvement of all relevant disciplines in the formulation of theories, identification of data, and in the model development. We provide recommendations for interdisciplinary model development, communication, and documentation to increase our understanding of fisheries as SES.